Answer:
C. [tex]cos^2A -sin^2A[/tex]
Step-by-step explanation:
Given:
[tex]cos2A[/tex]
To find:
The given expression is equivalent to:
A. [tex]sin^2A-cos^2A[/tex]
B. [tex]sin^2A+cos^2A[/tex]
C. [tex]cos^2A -sin^2A[/tex]
D. [tex]cosA-sinA[/tex]
Solution/Proof:
First of all, let us have a look at the compound angle formula for [tex]cos(X+Y)[/tex].
Compound angle means in which there is sum of two angles given.
In the above we are having X+Y i.e. sum of two angles X and Y. So it is compound angle.
The compound angle formula for cosine is given as:
[tex]\bold{cos(X+Y)=cosXcosY-sinXsinY}[/tex]
Here, let us put X = Y = A
[tex]cos(A+A)=cosAcosA-sinAsinA\\\Rightarrow \bold{cos(2A)=cos^2A-sin^2A}[/tex]
So, cos2A is equivalent to [tex]cos^2A -sin^2A[/tex].
Correct answer is:
Option C. [tex]cos^2A -sin^2A[/tex]